THE INTERTWINED RELATIONSHIP BETWEEN THE NAFS (CARNAL SOUL), AQL (REASONING) QALB (HEART) - Hyder Gulam (Islam Futura, 2018)
In a human being, each of nafs (carnal soul) aql (reasoning) and qalb (heart) have an important role to play in the development and make-up of a person. This paper will exploreIn detail the meaning of each of these key terms. This paper will then critically analyse the multifaceted relationship between these key terms, and what is the purpose of these terms with reference to the human being. These three terms have a distinct purpose, and are only but part of the constellation that make up the purpose of the human being and their soul. It is argued, that when harmoniously combined they form a greater unified purpose, in an effective and efficient relationship these terms lead to the sincere worship of God.